Situation Needs Analysis and Assessment Report: Ekxang Village - Grant, Angela; Mienmany S; Keophoxay, Anousith; Khodyhotha, Khamphamy; Phonevisay S; Souvannaxayyavong, Chantha; Toummavong, Phetsamone; Chidvilaphone, Saythong; Villanueva J; Khamkhosy, Neeny; Pavelic, Paul; Bouapao, Lilao; et al. (2015)
Ekxang village is located in the plains of Phonhong district, Vientiane province, Lao PDR. Since the 1990’s, the province has been under rapid infrastructural, economic and social development. Increased access to services including electricity, water, major roads, and education facilitated economic growth in the region. Employment in non-farming activities such as civil servants and factory workers is on the rise, particularly among men. Most of the provincial population (77%) is still dependent on agriculture as their main livelihood activity and rely heavily on natural resources for food security. The main crop produced in Vientiane province is rice (lowland 39.2%, upland 41.5% and plateau 19.3%) with other important crops including tamarind, mango, maize and rubber. Agricultural yields in the region are low but have the potential to increase through the use of supplemental irrigation, new varieties, improved production techniques and the adoption of climate smart technologies. A major threat to agriculture, food security and livelihoods in the region is climate change. The government of Lao PDR recognizes climate change as a barrier to the country’s overall development and has adopted several strategies for promoting adaptation and mitigation across various sectors. However, the ability of the country to adapt depends greatly on the capacity of its institutions to plan and implement these strategies. This study suggests that priority interventions to increase agriculture, food security and improve livelihoods in Ekxang CSV and, on a larger scale, Vientiane province, are 1) develop a sustainable water supply for irrigation, 2) diversify and increase production, 3) build the capacity of local organizations/staff, 4) support projects that focus on skills transfer to local staff and students, 5) enhance current local natural resource management initiatives, and 6) strengthen civil society.